The impact of preoperative breast MRI on the therapeutic management of breast cancer patients - Goren, Zohar; Zioni, Tammy; Lev, Dina; Cohen, Yaron; Perry, Zvi Howard (Surgical oncology, 2024)
The role of preoperative breast MRI to evaluate the extent of disease in breast cancer patients is considered controversial. We aimed at assessing the effect of breast MRI on the management of newly diagnosed breast cancer. A retrospective review of 202 consecutively seen patients who were newly diagnosed with breast cancer and who underwent preoperative breast MRIs at Assuta Ashdod between June 1, 2017, and June 1, 2020. Data included discovering suspicious lesions by conventional imaging, MRI findings, and surgical pathology results. This was analyzed to determine whether the MRI changed the management and whether it had a justified or unjustified effect on the treatment. The mean age was 54.51 (standard deviation, 11.34 years). Breast MRI revealed additional findings in 56 % of patients and modified therapeutic management in 32 % of the cases evaluated, having a justified effect in 87.6 %. Patients with changed management had a statistically significantly higher mastectomy rate (36 %) than those who did not (14 %). No statistically significant association was found between independent variables such as breast density, tumor location on the breast, type of tumor, patient's demographic information, etc. And whether MRI findings changed the initial treatment plan. MRI played an essential role in the preoperative staging of breast cancer in our study, modifying therapeutic planning in approximately one-third of the cases and having a justified effect on most of them. We, therefore, support preoperative breast MRI in newly diagnosed breast cancer patients. •We assessed the effect of MRI on the management of newly diagnosed breast cancer.•This was a retrospective review of 202 patients who were newly diagnosed with breast cancer and underwent a pre-op MRI.•Pre-op MRI revealed additional findings in 56% of the patients and modified the therapeutic choice in 32% of the patients, a positive effect of 88%.•MRI had an important role in pre-op staging of breast cancer, modifying therapeutic planning in a 1/3 of them, having a positive effect in most cases.